Hubungan Adversity Quotient dalam Komunikasi Organisasi dengan Motivasi Kerja Karyawan - Kurniadi, Endrian (UPT Publikasi Ilmiah UNISBA, 2023)
Abstract. The quantitative research backgrounded from government strategy related to holdingisasi. Researcher has interest to measuring the depth of adversity level employees, especially comparing between the leadership ranks and staff rank. The theory used in this research is the Adversity Quotient theory that proposed by Stoltz, and has been modified with self-concept heory and organizational communication theory to be adapted to the needs of the research and Work Motivation theory proposed by Keith & Newstroom. This study will examine the correlation of four subvariable Adversity with four subvariable Motivation, and then it will resulted in sixteen minor hypotheses and one major hypothesis. results of more specific research about the correlation of each subvariable, there are that can be applied to the population and there are only valid for the sample. There is a gap large enough for AQ value between the positions of leaders and positions of staff. Where the value of the correlation coefficient leader who is always in the same direction (the greater AQ the greater the motivation), is inversely proportional to the value of the correlation coefficient belong to staff